Pengaruh Pemberian Tepung Daun Kelor Pada Ibu Hamil Terhadap Kadar Malondialdehid (MDA) - Misrawati Misrawati; Marliah Marliah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; in normal pregnancy accompanied by increased metabolism and the high oxygen demand for tissue oxygen which can result in increased oxidative stress. The aim was to determine the effect of giving Fe and Moringa leaf meal on malondialdehyde levels in pregnant women. Method; pure experimental design with pre-test and post-test design with a control group. The results showed that there was an effect of Moringa leaf powder on levels of malondialdehyde after implementation with a p-value of 0.028. In the Fe group after implementation with a p-value of 0.492. There was no effect of iron administration on MDA levels. After implementation, the average reduction in malondialdehyde levels in the Moringa leaf meal group was 2.16 ± 2.21 nmol/ml, the Fe group was -0.42 ± -1.65nmol / ml. Conclusions; giving Moringa leaf flour can reduce levels of malondialdehyde in pregnant women